Studi Perbandingan Kurikulum Finlandia dan Indonesia: Upaya Peningkatan Kemampuan Pemecahan Masalah Matematika Siswa SMA - Hidayati, Destia Wahyu; Junaedi, Iwan; Mulyono (Circle: Jurnal Pendidikan Matematika, 2025)
Problem-solving ability is one of the abilities developed in the mathematics curriculum in various countries. The purpose of this study was to (1) determine the proportion of support for improving problem-solving abilities in high school mathematics curriculum documents in Finland and Indonesia, (2) determine the comparison of support in improving problem-solving abilities in high school mathematics curriculum documents in Finland and Indonesia. The method of this study is Study Literature Review (SLR). The data collection technique is documentation. The data analysis technique used is meta-synthesis with a meta-aggregation approach. The results of the study obtained (1) the proportion of problem-solving abilities in the components of the high school mathematics curriculum in both Finland and Indonesia was 44%. (2) the similarities between the Finnish and Indonesian curricula at the high school level to improve mathematical problem-solving abilities are in the aspect of mathematics learning, there are transversal components, there are general objectives and study objectives/learning achievements, the availability of modules and assessments, while the differences between the Finnish and Indonesian curricula at the high school level to improve mathematical problem-solving abilities are in the components of mathematical objectives and evaluation. In Indonesia, problem solving is one of the focuses of general mathematics objectives. Although in Finland the general objectives of mathematics do not include problem solving, they appear in each study objective. In the Finnish curriculum, the focus of evaluation includes problem solving and the obligation to use technology in evaluation, while in the Indonesian curriculum, evaluation is focused on initial, process, and final learning assessments.